Pengaruh Ekstrakurikuler Pencak Silat Terhadap Pendidikan Karakter Siswa di Mts Darul Falah Kabupaten Tulungagung - Dedy Firman Maulana; Anggoro Putranto (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
This research is motivated by the rampant criminal cases committed by members of martial arts schools in Indonesia, especially in East Java. This phenomenon includes brawls between martial arts schools, with the majority of the perpetrators still being students. This criminal act reflects reprehensible behavior and does not reflect the attitude of an educated student. In this study, a quantitative approach was used with a survey method involving the use of questionnaires and documentation. The research sample consisted of 65 students who were active in pencak silat martial extracurriculars. The results of the study showed that most of the 65 students at MTs Darul Falah Bendiljati Kulon Sumbergempol had good character, with 64 students in the fair category (scores 47-73) and only 1 student in the low category (scores 20-46). The average score of the student character questionnaire was 58.78. The results of the analysis also showed that pencak silat martial arts extracurricular had a significant influence on the formation of students' character, marked by a t_hitung score of 5,901 which exceeded the t_tabel score of 1,998, showing a positive contribution of this extracurricular in improving students' character.